Group Relations Consulting: Voice Notes from Robben Island - Flotman, Aden-Paul (The Indo-Pacific journal of phenomenology, 2018)
Group process consultants use themselves as instruments of intervention at the micro, meso and macro levels, and therefore need to have a deep sense of personal self-awareness and self-regulation as they serve as complex dynamic containers of group consultation processes. In this paper, I proceed from an ethnographic perspective to describe, reflect on and explore my emotional and cognitive lived experiences as consultant to participants' diversity encounters during a Robben Island Diversity Experience (RIDE) event in South Africa. Nineteen participants attended the event. It became clear that discussions were enhanced when the consultant was able to tap into somatic experiences as an additional source of information. The understanding of my consulting role experience may assist both current and emerging consultants in this and similar paradigms to gain insight into the impact of their own psychological disposition and socio-demographic profiles in contributing towards the deconstruction or formation of a good-enough consulting container.